Stability of Auger final dicationic states of core-ionized N2 molecules studied by Auger-electron ion coincidence measurements. (August 2015) - Iwayama, Hiroshi; Shigemasa, Eiji
Synopsis: We present experimental results for AEPICO measurements following core photoionization of N2 molecules, with using an AEPICO spectrometer in which a toroidal electron energy analyzer and an ion momentum spectrometer are installed.